Byzantine art - Cormack, Robin (Oxford ; New York : Oxford University Press, 2000)
An introduction to the whole range of Byzantine art explains the era's political and social developments, while examining the icons, illuminated manuscripts, mosaics, wall paintings, and other opulent works of the period.
Rome with a Christian face? : Early Byzantine art, 330-527 -- In the shadow of St. Sophia : Byzantine art in the sixth century and its aftermath, 527-680 -- The definition of an orthodox Christian empire : Byzantine art, 680-843 -- Developments and diversions in the consolidated empire : Middle Byzantine art, 843-1071 -- The new spirituality of the eleventh century and the world of the twelfth century -- Art in the service of failing society : Late Byzantine art, 1204-1453.
Includes bibliographical references (pages 231-237) and index.
Keywords: Art, Byzantine